PKR regulates LPS‐induced osteoclast formation and bone destruction in vitro and in vivo. (24th November 2016) - Teramachi, J; Inagaki, Y; Shinohara, H; Okamura, H; Yang, D; Ochiai, K; Baba, R; Morimoto, H; Nagata, T; Haneji, T
Abstract : Objective: In this study, we aimed to clarify the precise mechanism underlying lipopolysaccharide (LPS)‐induced osteoclastogenesis in periodontal disease with a special reference to double‐stranded RNA‐dependent protein kinase (PKR). Material and Methods: We dissected the role of PKR in LPS‐induced osteoclast differentiation and function using primary mouse bone marrow cells and RAW264.7 pre‐osteoclastic cell line. We used a rat experimental periodontitis (PD) model induced by ligature placement with a Porphyromonas gingivalis LPS injection (PD rat) and analyzed the therapeutic effects of C16, a PKR inhibitor, on bone loss in PD rats. Results: Protein kinase is strongly upregulated and phosphorylated by LPS in the osteoclasts. The inhibition of PKR suppressed LPS‐stimulated osteoclast formation and activation. PKR inhibition also suppressed the LPS‐mediated activation of NF‐ κ B and MAPK, which are critical pathways for osteoclastogenesis. High expressions of PKR were detected in osteoclasts of PD rats, and the treatment with C16 effectively prevented alveolar bone destruction in PD rats. Conclusions: PKR plays a pivotal role in LPS‐induced bone loss in PD and, thus, has potential as a therapeutic target for PD.